IMPLEMENTASI KEBIJAKAN UPAH MINIMUM KABUPATEN (UMK) DAN PENGARUHNYA TERHADAP KESEJAHTERAAN MASYARAKAT (Studi Pada Kabupaten Kebumen) - Prasetyo, Hendrawan (P4M STIE Putra Bangsa, 2018)
Almost the average company in Kebumen Regency has applied salary payment of employees in accordance with the provisions of MSEs, although in implementation is not one hundred percent. Although Kebumen District Government has set District Minimum Wage (MSE) in 2017 amounting to Rp 1,433,900.00, but there are still many employers / companies that pay salaries under the MSEs. The relations of workers and employers actually need each other. Workers expect the fulfillment of the necessities of life and the entrepreneur seeks to maintain the survival of his company. Without employers, workers find it difficult to sustain their lives, whereas unemployed workers will not be able to continue their business. So it needs a good relationship between the two, the existence of mutual understanding. Employers need to understand the needs of the workers, and the workers understand the company's ability to pay wages. The purpose of this study is to find out how the implementation of District Minimum Wage policy and its impact on community welfare in Kebumen District. The type of this research is qualitative research, taking the data source using the technique of